To change not to drown: Eurasian Oystercatchers Haematopus ostralegus adopt pole tops as safe nesting sites in the Lagoon of Venice (Avocetta, 2024)
Eurasian Oystercatchers have increasingly adopted pole tops in the last decade in the Lagoon of Venice (NE Italy). At the end of the study, 7% of the breeding population of the Lagoon (n = 180) nested on pole tops. Nests built in these structures are safe from flooding due to extremely high tides, thus allowing a high hatching success: 42 clutches out of 43 (97.7%) hatched. We hypothesise that this is an adaptive behaviour to the increased frequency of extreme high tides in the last decade and is a good omen for the species. The good availability of pole tops suitable for nesting in the Lagoon allows breeding in areas otherwise unsuitable for nesting due to the lack of sites safe from flooding. Placement of artificial nests on pole tops is also feasible and could be an easy and cheap strategy for the conservation of the breeding population of Oystercatchers in the Lagoon of Venice as extreme high tides and spring storms will likely increase in the future.
Keywords: sea level rise; Lagoon of Venice; Haematopus ostralegus; Eurasian Oystercatcher; breeding